(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Chia seeds are abundant in lipids (30–33%) and carbohydrates (26–41%), proteins (15–25%), vitamins, minerals, antioxidants, and dietary fibre (18–30%) (wet basis). Numerous studies on phytochemicals have been published, emphasizing that polyunsaturated fatty acids (PUFAs) including linoleic (LA, ω-6 fatty acid) and α-linolenic (ALA, ω-3 fatty acid) are the primary ingredients of chia oil. The current study aimed to assess and contrast the hepatoprotective potential of chia seed oil with that of silymarin in a rat model of paracetamol-induced hepatotoxicity. Paracetamol is known to cause acute liver injury at high doses, primarily through oxidative stress and the formation of reactive metabolites. To evaluate the degree of hepatic protection offered by the treatments, comprehensive biochemical assays and histopathological evaluations were carried out. This study confirms that paracetamol induces significant liver toxicity as demonstrated by elevated biochemical markers and severe histological damage. Silymarin, a well-established hepatoprotective agent, effectively mitigates this damage, restoring both biochemical and histological profiles to near-normal. Chia seed oil also exhibits hepatoprotective properties, likely owing to its abundant omega-3 fatty acids and antioxidant constituents, although its efficacy is slightly lower compared to silymarin. Therefore, chia seed oil may serve as a promising natural hepatoprotective supplement, especially when silymarin is contraindicated or unavailable. Further studies focusing on dose optimization, bioavailability, and long-term efficacy of chia seed oil are warranted to validate its therapeutic potential in clinical settings. While the current study provides strong preliminary evidence of the hepatoprotective effect of chia seed oil, addressing its limitations and expanding the research scope will be critical for clinical application and regulatory acceptance.